IMPROVING PUBLIC SERVICE QUALITY THROUGH CITIZENSâ PARTICIPATION - Naibaho, Veronika Hanna (FIA UB, 2013)
Abstract: Improving Public Service Quality Through Citizensâ Participation. As the capacity of government is being questioned for not delivering public services effectively and efficiently, the government nowadays are pursuing for accountability and democracy. They want to create good governance. Public service is one way to represent governmentâs performance. In public sectors, service providers through the street-level civil servants interact with citizens as service users. Consequently, implementing State Minister of Administrative Reform Regulation Number 13 Year 2009 concerning the method of improving public service quality through citizensâ participation remains a very important aspect in government organizations like Abdul Wahab Sjahranie hospital. Utilizing qualitative method, this research identifies the improvements of public service quality in the hospital. by evaluating the implementation of the regulation. Based on the result of achievements, outputs of the project are achieved and a number of positive changes have been identified in the hospital. Â Keywords: improving public service quality, abdul wahab sjahranie hospital, evaluation. Â Abstrak: Meningkatkan Kualitas Pelayanan Publik Melalui Partisipasi Masyarakat. Saat ini, kapasitas pemerintah dipertanyakan karena tidak memberikan pelayanan publik secara efektif dan efisien. Untuk itu, dalam rangka mewujudkan tata kepemerintahan yang baik, pemerintah ingin agar dapat melayani secara akuntabel dan demokratis. Pelayanan publik merupakan representasi kinerja pemerintah karena di sektor publik karena disinilah penyedia layanan melalui frontliners-nya berinteraksi dengan masyarakat pengguna layanan. Oleh karena itu, implementasi Peraturan Menteri Negara Pendayagunaan Aparatur Negara Nomor 13 Tahun 2009 tentang Metode Peningkatan Kualitas Pelayanan Publik Melalui Partisipasi Masyarakat menjadi aspek yang sangat penting dalam organisasi pemerintah seperti Rumah Sakit Umum Daerah Abdul Wahab Sjahranie. Dengan menggunakan metode kualitatif, penelitian ini mengidentifikasi perbaikan kualitas pelayanan publik di RSUD AW Sjahranie dengan mengevaluasi pelaksanaan peraturan tersebut. Berdasarkan hasil evaluasi, output kegiatan tercapai dan sejumlah perubahan positif dapat diidentifikasi. Â Kata Kunci: peningkatan kualitas pelayanan publik, rumah sakit umum daerah abdul wahab sjahranie hospital, evaluasi.